Review of FUNDC1-mediated mitochondrial autophagy in Alzheimer’s disease - Shi, Dandan; Guo, Xiaochen; Ning, Ziqi; Zhang, Yaoyao; Liu, Fang; Liu, Meixia; Wei, Yun (Frontiers in Aging Neuroscience, 2025)
Mitochondrial autophagy is a critical quality control mechanism that eliminates dysfunctional mitochondria to maintain cellular homeostasis. Among receptor-dependent mitophagy pathways, FUN14 domain-containing 1 (FUNDC1)—a mitochondrial outer membrane protein harboring an LC3-interacting region (LIR)—plays a central role by directly binding to LC3 under stress conditions, thereby initiating autophagosome encapsulation of damaged organelles. Emerging evidence implicates FUNDC1 dysregulation in neurodegenerative diseases, particularly Alzheimer’s disease (AD), where defective mitophagy exacerbates hallmark pathologies including Aβ plaque deposition and hyperphosphorylated Tau-driven neurofibrillary tangles. Despite advances, the molecular interplay between FUNDC1 phosphorylation states (e.g., Ser13/Ser17/Tyr18) and AD progression remains poorly defined. This review systematically examines FUNDC1’s dual regulatory role in mitophagy, its mechanistic links to Aβ and Tau pathologies, and the therapeutic potential of targeting FUNDC1-associated kinases (e.g., ULK1, CK2) or downstream effectors (e.g., DRP1, OPA1) to counteract mitochondrial dysfunction in AD. By synthesizing recent preclinical and clinical findings, we aim to bridge the gap between FUNDC1 biology and AD therapeutics, highlighting actionable nodes for drug development.